2013
DOI: 10.1111/1365-2656.12130
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling pollen–transport networks to the level of individuals

Abstract: Summary1. Most plant-pollinator network studies are conducted at species level, whereas little is known about network patterns at the individual level. In fact, nodes in traditional speciesbased interaction networks are aggregates of individuals establishing the actual links observed in nature. Thus, emergent properties of interaction networks might be the result of mechanisms acting at the individual level. 2. Pollen loads carried by insect flower visitors from two mountain communities were studied to constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(143 citation statements)
references
References 65 publications
9
132
1
1
Order By: Relevance
“…Others have also distinguished between species-driven interaction turnover and rewiring [9,15], but because species-driven turnover was the main contributor, we further partitioned it into pollinator-, plant-and pollinator þ plant-driven (figures 1 and 3). Along the entire gradient, pollinator-driven turnover accounted for a larger fraction of the overall species-driven turnover than that of plants, which probably is an effect of (i) the initial selection of sites based on their vegetational similarity, (ii) the plant-centred sampling protocol where we observed plants for pollinators and not vice versa [42,43], (iii) the higher diversity of pollinators compared with plant species, and (iv) the perennial lifestyle of plants versus the annual lifestyle of the pollinators. Thus, pollinator species probably fluctuated more in abundance and diversity, and consequently accounted for more of the observed interaction turnover.…”
Section: Discussion (A) Community Similaritymentioning
confidence: 91%
“…Others have also distinguished between species-driven interaction turnover and rewiring [9,15], but because species-driven turnover was the main contributor, we further partitioned it into pollinator-, plant-and pollinator þ plant-driven (figures 1 and 3). Along the entire gradient, pollinator-driven turnover accounted for a larger fraction of the overall species-driven turnover than that of plants, which probably is an effect of (i) the initial selection of sites based on their vegetational similarity, (ii) the plant-centred sampling protocol where we observed plants for pollinators and not vice versa [42,43], (iii) the higher diversity of pollinators compared with plant species, and (iv) the perennial lifestyle of plants versus the annual lifestyle of the pollinators. Thus, pollinator species probably fluctuated more in abundance and diversity, and consequently accounted for more of the observed interaction turnover.…”
Section: Discussion (A) Community Similaritymentioning
confidence: 91%
“…We found that bees readily visited M. cardinalis flowers in monospecific greenhouse populations but mostly avoided them Foraging rate (no. Recent studies on plant-pollinator interaction networks have shown that individual specialization, although a common behavioral attribute in generalist pollinators, is often overlooked by traditional species-level indices of specialization (e.g., visitation rates to a focal plant) due to inter-individual variability in floral resource use (Tur et al 2014(Tur et al , 2015. Despite suggestions to the contrary Schemske 2003, Lunau et al 2011), bumble bees clearly have the capacity to detect bird syndrome flowers and learn to associate them with a nectar reward, a finding well supported by previous work (Chittka and Waser 1997, Mayfield et al 2001, Martinez-Harms et al 2010, but choose to avoid them in mixed floral environments when it makes economic sense to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Those results are in agreement with some experimental studies performed with fishes for which inter-individual variation increased with population density. Abundance also decreased intraspecific overlap in plant-pollinator networks (Tur et al 2014). In contrast, solitary species such as roe deer could be less prone to intra-specific competition, as each individual should be able to feed on their preferred resources without pressure from congeners in their close vicinity.…”
Section: Higher Inter-individual Variation For Social Species Supportmentioning
confidence: 97%